Challenges for immunotherapy for the treatment of platinum resistant ovarian cancer. (December 2021) - Le Saux, Olivia; Ray-Coquard, Isabelle; Labidi-Galy, S. Intidhar
Abstract: Platinum resistant ovarian cancer, usually defined as progression occurring within 6 months after completing platinum-based therapy, is a heterogeneous disease with poor prognosis and short survival (less than 18 months). It is typically considered as a "cold tumor", characterized by reduced infiltration by immune cells, particularly CD8 + T cells. Response rate to anti-PD1/PD-L1 monotherapy is low, not exceeding 8%. Multiple therapeutic strategies are currently investigated in order to increase response rates to anti-PD1/PD-L1 through adding chemotherapy, anti-angiogenic agents, DNA damage (PARP inhibitors, cyclophosphamide and/or radiotherapy) or other immune checkpoint inhibitors (CTLA-4, etc.). Ovarian clear cell carcinoma, a rare histotype characterized by primary platinum-resistance, recently showed anecdotal but promising response rates to immune checkpoint blockade. Other immunotherapeutic approaches such as adoptive T cell therapy, vaccines and targeting myeloid immune checkpoints like "don't eat me" signal CD47 are currently investigated. Each approach faces distinct challenges that will be reviewed here. Robust immunogenomics studies conducted in parallel of the ongoing trials will help into refining optimal immunotherapy combination for this lethal disease and identify predictive biomarkers.